1977
DOI: 10.3109/00365527709181679
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid Concentrations in Systemic and Portal Serum in Presumably Normal Man and in Cholestatic and Cirrhotic Conditions

Abstract: Total bile acid concentration was determined in systemic and portal serum and in liver tissue from patients with presumably normal liver function, and from patients with extrahepatic cholestasis. Systemic and portal serum bile acids were also determined in patients with alcoholic liver cirrhosis. In 5 patients, in whom a portal catheter was inserted through the umbilical vein, the diurnal variation in systemic and portal serum bile acid concentration was studied. In patients with presumably normal liver functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The additional possibility of a difference in the lymphatic transport between trihydroxy and dihydroxy bile acid has been raised by Lindblad et al. (23). However, recent studies on lymphatic bile acid transport in man demonstrated that <0.1% of bile acid enterohepatic circulation occurs via this route.…”
Section: Discussionmentioning
confidence: 94%
“…The additional possibility of a difference in the lymphatic transport between trihydroxy and dihydroxy bile acid has been raised by Lindblad et al. (23). However, recent studies on lymphatic bile acid transport in man demonstrated that <0.1% of bile acid enterohepatic circulation occurs via this route.…”
Section: Discussionmentioning
confidence: 94%
“…Understanding the mechanism behind these various effects of apoA-I is challenging, because it is diffi cult to differentiate a direct cellular effect of apoA-I on a cell-signaling pathway as opposed to an indirect effect from the cellular response from cholesterol effl ux. For example, apoA-I-mediated decrease of CD11 ␤ expression in mononuclear cells is replicated by methyl-␤ -cyclodextrin, suggesting that cholesterol by guest, on May 8, 2018 www.jlr.org Downloaded from kidney cells, which have minimal or no SR-BI expression, facilitated HDL transfer of functional miRNAs to cultured cells. HDL-mediated miRNA delivery was shown to affect the expression of luciferase reporter constructs containing the 3 ′ untranslated region of a putative mRNA target for the transferred miRNA ( 88 ).…”
Section: Hdl Proteomementioning
confidence: 99%
“…Likewise, HDL S1P has been found to repress the expression of endothelial adhesion molecules, cytotoxic to specifi c cells ( 34 ). Although BA concentrations in general circulation are relatively low compared with portal circulation, multiple physiologic conditions and diseases, such as cholestasis, hepatitis, and cirrhosis, have been found to substantially increase the amount of circulating BAs in blood (35)(36)(37)(38). Most BAs in the circulation are free or are bound to albumin; however, BAs are also found in lipoprotein fractions.…”
Section: Hdl Lipidomementioning
confidence: 99%
See 1 more Smart Citation
“…1 Cholestasis causes concentrations of bile acids to rapidly increase in liver and plasma. 3,4 As this disease progresses, hepatic inflammation and hepatocyte injury ultimately develop. 5 If cholestasis is not corrected and hepatocyte injury persists, portal myofibroblasts and hepatic stellate cells are stimulated to proliferate and produce extracellular matrix, a process that ultimately results in the development of biliary fibrosis and eventually cirrhosis.…”
mentioning
confidence: 99%